2020
DOI: 10.1634/theoncologist.2020-0305
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide, Dexamethasone, or Palonosetron for Prevention of Delayed Chemotherapy-Induced Nausea and Vomiting After Moderately Emetogenic Chemotherapy (MEDEA): A Randomized, Phase III, Noninferiority Trial

Abstract: Disclosures of potential conflicts of interest may be found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Due to the multiple adverse effects of chemotherapeutic agents, a combination of antiemetic agents must be tested, such as preventing the stimulation of dopamine D2 receptor in the chemoreceptor trigger zone (CTZ) and binding neurokinin-1 (NK-1) receptor with substance P in the area postrema. 19,20 Although the addition of a corticosteroid improves the potency of 5-HT3 receptor antagonists against CINV in different clinical trials, the best standard single-dose treatment with 5-HT3 receptor antagonists for pediatric emesis has not yet been demonstrated, particularly in the acute chemotherapy phase, i.e., the first 24 h. Few studies have reported the potency of a dopamine D2 receptor antagonist in the prevention of acute emesis 9 ; however, the guidelines for the prevention of CINV do not consider those regimens due to faults in the study design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the multiple adverse effects of chemotherapeutic agents, a combination of antiemetic agents must be tested, such as preventing the stimulation of dopamine D2 receptor in the chemoreceptor trigger zone (CTZ) and binding neurokinin-1 (NK-1) receptor with substance P in the area postrema. 19,20 Although the addition of a corticosteroid improves the potency of 5-HT3 receptor antagonists against CINV in different clinical trials, the best standard single-dose treatment with 5-HT3 receptor antagonists for pediatric emesis has not yet been demonstrated, particularly in the acute chemotherapy phase, i.e., the first 24 h. Few studies have reported the potency of a dopamine D2 receptor antagonist in the prevention of acute emesis 9 ; however, the guidelines for the prevention of CINV do not consider those regimens due to faults in the study design.…”
Section: Discussionmentioning
confidence: 99%
“…9 Palonosetron at fixed doses has been found to be safe and potent enough to prevent CINV, whether acute or delayed, in adults. 20 However, there is no consensus on using palonosetron at fixed doses in pediatric patients receiving chemotherapy for various malignancies. Recently, the POGO and Multinational Association of Supportive Care in Cancer/European Society for Medical Oncology (MASCC/ESMO) guidelines have been released on the inclusion of palonosetron for pediatric patients receiving MEC and HEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, all patients were administered metoclopramide for 5 days, which is approved as prophylaxis for delayed emesis in Korea. Although metoclopramide is not recommended as prophylaxis in the recent guidelines, it aids with managing delayed or breakthrough emesis [ 4 , 25 , 26 ]. Since our study focused on the delayed phase, we decided to use a combination of all available drugs that can prevent and/or relieve possible symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 25 years, major advances in nausea and vomiting reduction from chemotherapy and/or radiation therapy have improved this situation. These include the following: common use of selective serotonin receptor (5-HT3 also known as 5HT) antagonists for immediate N/V, neurokinin receptor antagonists (aprepitant and fosaprepitant) for delayed nausea, and the recognition of corticosteroids and olanzapine in front-line anti-emetic regimens for chemotherapy and radiation [19,21,[84][85][86][87][88]. Although N/V from chemotherapy and/or radiation remains common, there are many effective strategies to ameliorate N/V and improve eating behaviors during chemotherapy and radiation as detailed in Table 3.…”
Section: Nausea As a Source Of Poor Appetite: Approaches To Reduce Nauseamentioning
confidence: 99%